2018
DOI: 10.1182/blood-2017-10-811224
|View full text |Cite
|
Sign up to set email alerts
|

Interim results of brentuximab vedotin in combination with nivolumab in patients with relapsed or refractory Hodgkin lymphoma

Abstract: In this phase 1/2 study, brentuximab vedotin (BV) and nivolumab (Nivo) administered in combination were evaluated as initial salvage therapy in patients with relapsed or refractory (R/R) classical Hodgkin lymphoma (HL). Patients received up to 4 cycles of combination treatment, with BV administered on day 1 and Nivo on day 8 of the first cycle. For cycles 2 to 4, BV and Nivo were both administered on day 1. After study treatment, responses were evaluated by investigators per the 2014 Lugano classification, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
197
0
12

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 282 publications
(214 citation statements)
references
References 49 publications
5
197
0
12
Order By: Relevance
“…Various clinical trials are currently ongoing to evaluate the efficacy and safety of such combinatory approaches, also in patients with cHL. Early results of 62 patients with r/r cHL treated with BV and nivolumab in a phase I/II study reported an ORR 85% with a 64% CRR and irAEs °3 occurring in < 5% of patients [47]. Similar results were also observed among 19 patients treated with the same combination in another phase I trial (ORR 89%, CRR 50%), with 2 (10.5%) cases of severe pneumonitis observed [48].…”
Section: Combinatory Approachessupporting
confidence: 70%
“…Various clinical trials are currently ongoing to evaluate the efficacy and safety of such combinatory approaches, also in patients with cHL. Early results of 62 patients with r/r cHL treated with BV and nivolumab in a phase I/II study reported an ORR 85% with a 64% CRR and irAEs °3 occurring in < 5% of patients [47]. Similar results were also observed among 19 patients treated with the same combination in another phase I trial (ORR 89%, CRR 50%), with 2 (10.5%) cases of severe pneumonitis observed [48].…”
Section: Combinatory Approachessupporting
confidence: 70%
“…Consequently, antibodies against PD‐1 have shown remarkable efficacy in relapsed/refractory HL and compounds, such as nivolumab and pembrolizumab, are therefore likely candidates for older patients (Ansell et al , ; Younes et al , ; Chen et al , ). Although, again, trials testing nivolumab and pembrolizumab included only a few older patients, the antibodies had little toxicity compared to chemotherapy, and trials testing combinations brentuximab vedotin and nivolumab are currently recruiting (Herrera et al , ).…”
Section: Novel Substancesmentioning
confidence: 99%
“…Moreover, anti‐PD1 agents may enhance the response rates of pre‐ASCT single‐agent BV, as documented in earlier trials (Chen et al , 2015a; Moskowitz et al , 2015a). Herrera et al () conducted a phase 1/2 trial of BV in combination with nivolumab (Nivo‐BV) in patients with relapsed and refractory HL failing induction therapy. BV was delivered at the standard dose of 1·8 mg/kg on day 1 and nivolumab was given at the dose of 3·0 mg/kg (on day 8 on cycle 1, then on day 1); each cycle was repeated every 21 days, for up to 4 cycles.…”
Section: The Pre‐autologous Setting: Boosting Responses Before Transpmentioning
confidence: 99%